Impact of Academic Stress on Secondary School Student’s Performance: A Qualitative Exploration (Journal of Asian Development Studies, 2023)
The study investigates the influence of teaching methods, the school environment, and the home environment on academic stress. Future concerns related to career choices are also explored. Thematic analysis is applied to discern patterns from interviews, with a primary goal of understanding how academic stress impacts student performance. The paper discusses various contributors to academic stress, including teacher expectations and the school environment. Utilizing a qualitative research design, the study employs purposive sampling across ten public secondary schools in the Vehari district. Semi-structured interviews with students are conducted, targeting a sample of ten students from five schools. Data collection involves face-to-face interviews, recorded and transcribed for thematic analysis. The conclusion summarizes the pervasive nature of academic stress and highlights students' delicate balance. Coping mechanisms, especially a supportive home study environment, are emphasized. The study concludes with practical recommendations for teachers, emphasizing constructive feedback and the creation of an equitable and supportive classroom atmosphere.